Pengaruh Program Perubahan Perilaku Ibu Hamil (Cerdigi) Berdasarkan Teori ABC (Studi Pendahuluan di Kelurahan Serpong, Tangerang Selatan) - Annisa Septalita; Peter Andreas (Faculty of Dentistry, Universitas Gadjah Mada, 2015)
Maternal Behavior Change Program (Cerdigi) Based on ABC’s Theory (Pilot Study in Serpong Subdistrict, South Tangerang). Oral health is one of the things that need attention during pregnancy. However, the behavior of dental and oral health maintenance during pregnancy is still low. Poor oral health conditions in pregnant women can have an impact, such as premature births and low birth weight (LBW) babies. ABC behavior change theory focuses on the antecedent, behavior, and consequence of behavior. The purpose of this study is to determine pregnant women’s behavior of oral health maintenance, identify their antecedent factors, behavior change interventions (DHE), and analyze the behavior consequence. This was a descriptive research with a cross-sectional design among 27 pregnant women in Serpong Subdistrict, South Tangerang. The data were collected through interviews and questionnaires. The results show 100% (27 respondents) did tooth brushing twice a day, 44,4% (12 respondents) used mouthwash once a week and 4% (1 respondent) visited a dentist during pregnancy. The antecedent factors of not visiting a dentist during pregnancy were because: 33% did not know the benefits of visiting a dentist, 26% had fear of dentist, 19% felt that visiting a dentist was expensive, 11% did not feel the need to go to a dentist, and 11% had fear of disturbing the fetus. After 9 days of intervention, the consequences on the 19 respondents were evaluated and the results show that 89.5% had not visited a dentist, 5.25% had visited a dentist, and 5.25% did not want to visit a dentist. The reason of not visiting a dentist was because of having not much time 52.8%, having nobody to accompany 11.8%, feeling lazy 11.8%, still feeling afraid of a dentist 11.8 %, and having no money 11.8%. The conclusion from this study is that the most dominant behaviors of oral health maintenance in pregnant women is to maintain it by themselves (toothbrushing and using mouthwash), while maintaining the health by visiting a dentist is still low with various antecendents.